2017
DOI: 10.1002/ase.1699
|View full text |Cite
|
Sign up to set email alerts
|

Learning from human cadaveric prosections: Examining anxiety in speech therapy students

Abstract: Human anatomy education often utilizes the essential practices of cadaver dissection and examination of prosected specimens. However, these exposures to human cadavers and confronting death can be stressful and anxiety-inducing for students. This study aims to understand the attitudes, reactions, fears, and states of anxiety that speech therapy students experience in the dissection room. To that end, a before-and-after cross-sectional analysis was conducted with speech therapy students undertaking a dissection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 37 publications
2
32
2
3
Order By: Relevance
“…Two anonymous questionnaires ("ad hoc", STAI) were carried out before and after the first practice. The "ad hoc" questionnaire assessed each student's feelings, emotions and satisfaction with this practice [15,17]. These questionnaires were completed by the students themselves so that they could be combined with a second questionnaire that was completed immediately after the practice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two anonymous questionnaires ("ad hoc", STAI) were carried out before and after the first practice. The "ad hoc" questionnaire assessed each student's feelings, emotions and satisfaction with this practice [15,17]. These questionnaires were completed by the students themselves so that they could be combined with a second questionnaire that was completed immediately after the practice.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, several questions about the degree of satisfaction with the class and its quality were also included [15,17,18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…F2F and online content were also supplemented with 3 hours of weekly F2F practical sessions so as to not leave students feeling isolated in their learning. Two hours were dedicated to students having access to prosected cadaveric specimens, anatomical models, skeletons, plastinated cross‐sections, and X‐rays (Nnodim, ; Criado‐Álvarez et al, ). The third hour of the practical session involved students completing further guided activities designed to consolidate their understanding of the anatomical content.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of scientific issues was shown that at the differentiated studying of autonomic disorders depending on localization of the stroke, patients with right-sided process have vagotonic disturbances with depression of a tonus of veins, arterioles more often, and also with activation of a limbic system [2,9,10,13]. In patients with the stroke in the left hemisphere the simpaticotonia with increasing of peripheral resistance of vessels, a vascular tonus, difficulty of venous outflow was observed [6].…”
mentioning
confidence: 99%